PARTNERSHIP STRATEGY AND COMPETITIVE ADVANTAGE TO IMPROVE THE PERFORMANCE OF MSMEs IN THE CREATIVE INDUSTRY - Ratnawati, Ratnawati (Jurnal Aplikasi Manajemen, 2019)
The purpose of this study is to examine the effect of partnership strategies on the performance of creative industries through competitive advantage. The population of this research is Micro, Small, and Medium Enterprises (MSMEs) in Malang City, amounting to 113,000 units in 2018 (in food processing, handicraft, agriculture, and clothing). The respondents are the owners of MSMEs because they can provide information based on the objectives of this research. The number of samples in this study was taken using Slovin's formula, with a sampling error rate of 5%. The total number of sample obtained was 100 MSMEs. The sample was taken using random sampling method. The analytical method used was Structural Equation Modeling (SEM). The results showed that partnership strategy affects competitive advantage. Competitive advantage can mediate the effect of partnership strategy on MSME performance.